Austenite decomposition of C-Mn steel containing boron by continuous cooling - Garlipp, W.; Cilense, M.; Gomes, SIN (Elsevier B.V., 2001)
The austenite decomposition in C-Mn steel containing boron was studied by continuous cooling from 1100 and 845 degreesC using the Jominy test. The results indicate that the different cooling speeds and the presence of boron refine and change the percentage of ferrite microstructure, martensite, and fine pearlite. (C) 2001 Elsevier B.V. B.V. All rights reserved.
Keywords: C-Mn steel with boron addition; austenite decomposition; TTT and CCT diagrams; Jominy test